Translating Arabic Aphorismsi into Indonesian Language: Its Strategies and Equivalence | Tarjamah Al-Hikam Al-'Arabīyah ilā Al-Lughah Al-Indūnīsīyāh: Istirātījīyātuhā wa At-Takāfu' Fīhā - Zainal Muttaqin; N. Lalah Alawiyah; Awalia Rahmi Zahara; Fatima El Zahraa (Al-Ta'rib, 2022)
This research aims to reveal the strategies used in translating Arabic aphorisms into Indonesian language and to measure the equivalence at word level in the book entitled Seratus Mahfudzot written by As’ad Humam (1994). This qualitative study was performed in a descriptive analysis based on the theory of translation strategies which were limited to structural and semantic strategies of Suryawinata and Hariyanto (2003) and the theory of equivalence at word level of Baker (2001). Triangulation of data sources was used to validate research findings. From 150 words that have been analyzed, the results highlighted 9 strategies that were applied as followed: 60 (40%) additions, 16 (10.67%) subtractions, 22 (14.67%) transpositions, 4 (2.67%) modulations, 32 (21.33%) borrowings, 5 (3.33%) cultural equivalents, 3 (2%) synonyms, 3 (2%) reductions, and 5 (3.33%) expansions. The equivalence at word level reached 74%, whereas 26% were found non-equivalent. It strengthens the assumption that there are characteristic difference and similarity between Arabic and Indonesian to take into consideration in translation.